A Study to Assess the Effectiveness of Video Assisted Teaching (VAT) on Knowledge of Environmental Hygiene in Rural Community - Anjumole Varghese1 , Babli Shama1 ; Dalvi Vinaya Anil1 , Bhosale Pooja Bhosale1 ; Kangude Shivdas1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction : Environmental hygiene is a major public health issue in Indian community. Knowledgeon environmental hygiene in rural community is one of the most effective ways to solve this publichealth issues. The aim of this the study is to assess the effectiveness of video assisting teaching (VAT) onknowledge of environmental hygiene among rural community This paper discusses teaching interventionand implementation strategies related to environmental hygiene in Indian emphasizes to prioritize itaccording to the need of the country. Aim: To assess the effectiveness of video assisting teaching (VAT)on knowledge of environmental hygiene among rural community Materials and methods: Quantitativeexperimental approach (pretest posttest one group design) was applied to find out the effectiveness of videoassisted teaching (VAT) on knowledge of environmental hygiene in rural community. Convenience samplingtechnique used to select the 150 sample for the study. Results: Average pretest score was 12.45 and posttestscore was 20.54 where the standard deviation of pretest is 3.30 and posttest is 2.53. Range of pretest scoreis 4 – 20. After video assisted teaching, the range of posttest is 11 – 26 (median of pretest is 13 and posttestmedian is 21). There was a significant difference between pretest and posttest knowledge score of 8.9, sowe support and accept alternate hypothesis. Conclusion: Video Assisting Teaching (VAT) is an effectivemethod to teach the people of rural community.